Antidepressant-Like Effect of Lipid Extract of Channa striatus in Postpartum Model of Depression in Rats. (29th November 2017) - Abdul Shukkoor, Mohamed Saleem; Baharuldin, Mohamad Taufik Hidayat Bin; Mat Jais, Abdul Manan; Mohamad Moklas, Mohamad Aris; Fakurazi, Sharida; Basir, Rusliza
Abstract : Postpartum depression affects 15% of women. Channa striatus, a freshwater fish, is consumed in local Malay population as a rejuvenating diet during postpartum period. This study evaluated the antidepressant-like effect of lipid extract of C. striatus fillet and its mechanism of action in female Sprague-Dawley rats in postpartum model of depression. The rats were ovariectomized and treated with high dose of progesterone and estradiol benzoate for 23 days to have hormone-simulated pregnancy. The day 24 and afterwards were considered as the postpartum period. During the postpartum period, lipid extract was administered at 125, 250, and 500 mg/kg through intraperitoneal route for 15 days. Fluoxetine (10 mg/kg) was used as the positive control. On postpartum day 15, the animals were tested in forced swimming test (FST) and open field test (OFT) followed by biochemical analysis. Withdrawal of hormone administration during the postpartum period induced depressive-like behavior in FST. Administration of lipid extract reversed that depressive-like behavior at 125, 250, and 500 mg/kg in FST. In OFT, it decreased the exploratory activity. The mechanism of the antidepressant-like effect may be mediated through the decrease in plasma corticosterone, increase in plasma oxytocin, and decrease in nuclear factor-kappa B in prefrontal cortex of rats.